Intercultural learning on the Web Steps to the "cultures in-between" - Juliana Raffaghelli (Pensa MultiMedia, 2015)
This article presents a process of creation of a professional learning-community within a project of international cooperation among Turkey, Slovenia and Italy, which main goal was to promote teachers collaboration across frontiers for implementing innovation in class to promote intercultural dialogue. The creation, strategies and use of a virtual working/learning space (VWLS) to promote this process are hereby described. Furthermore, in this article I attempt to show how the VWLS can give support to intercultural dialogue, from motivation to participate and share the own cultural identity, to the process of working and learning together. In fact, the VWLS becomes meaningful, exposing teachers and students to an enlarged cultural context, diverse, but also comprehensive of the own original cultural context, because built semantically by themselves. This sense making process could impact on a new dimension of intercultural learning in a new place without frontiers, that is represented by "virtual" reality. Questions addressing this explorative and qualitative research work where: can the web spaces become place to promote intercultural learning? How these online spaces should be featured in terms of representation of cultural differences? How can they promote intercultural dialogue? And the most exciting: how can they allow processes of construction of new culturally hybrid meanings?